The Past, Present, and Future Trends of Biosorption - Park, D.H., Kyungpook National University, Daegu, Republic of Korea; Yun, Y.S., Chonbuk National University, Jeonju, Republic of Korea; Park, J.M., Pohang University of Science and Technology, Pohang, Republic of Korea (Biotechnology and bioprocess engineering, 2010)
The discovery and further development of biosorption phenomena provide a basis for a whole new technology aimed at the removal of various pollutants or the recovery of valuable resources from aqueous systems. Today, biosorption is one of the main components of environmental and bioresource technology. Since the status of scientific development of a technology can be reflected through analyses of the literatures pertaining to it, in this review, we qualitatively examine almost all aspects of biosorption research. A range of subjects are covered, including the initial history, raw materials, mechanisms, instrumental tools, process factors, modification and immobilization methods, recovery and regeneration, continuous processes, commercial application, and modeling studies of biosorption. Finally, we summarized the important considerations of the current research on biosorption, as well as the suggestions for its future directions. We believe that this review will prove to be useful for scientists and engineers in the performance of their research into biosorption.